A note on the cost of instability in whale management - Schwedeer, Tore; Hagen, Gro (J. Cetacean Res. Manage., 1999)
The history of whaling has been characterised by considerable variation in management ’philosophy’. For example, an early period of overexploitation led eventually to the present period of protectionism and might be followed by a period of excessive catches. Is such instability in long-term management costly? The risk of depletion increases with increasing instability. If the net production function governing whale dynamics is essentially convex, it is demonstrated that long-term catches are necessarily smaller the greater the management instability. A simulation experiment is carried out to quantify the loss in whale catches due to •stop-go’ instability in whale management. To examine possible costs in terms of fisheries for cod and herring, a multi-species simulation model is used, with minke whales managed by a stochastic stop-go procedure and with cod, herring and capelin managed by VPA-type procedures. In the simulations, whale catches are reduced by increased instability in whale management while long-term catches of cod and herring are unaffected, provided mean whale abundance is kept fixed.